PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Cen, Bui; Jonathan, Aries (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study is to obtain empirical evidence that financial performance, firm size, leverage, board of directors size, auditors size, share issuance activity, independent commissioner effect earnings management. The population used in this research are non financial companies listed in Indonesia Stock Exchange (IDX) with research period from 2018 to 2020, where there are 162 companies were successfully selected as research samples. The sample selection method used in this research is purposive sampling method while data were analyzed using multiple regression method. The result of this research shows that financial performance, auditors size, and independent commissioner have significant effect on earnings management. The result explains that high financial performance has the ability to generate high profits and it will tend to do the earnings management. The larger size of auditor and number of independent commissioners will increase supervision of the financial statements and it will prevent the earnings management practices. While firm size, leverage, board of directors size, and share issuance activity have no significant effect to earnings management.